2014
DOI: 10.1371/journal.pcbi.1003483
|View full text |Cite
|
Sign up to set email alerts
|

Pathway Thermodynamics Highlights Kinetic Obstacles in Central Metabolism

Abstract: In metabolism research, thermodynamics is usually used to determine the directionality of a reaction or the feasibility of a pathway. However, the relationship between thermodynamic potentials and fluxes is not limited to questions of directionality: thermodynamics also affects the kinetics of reactions through the flux-force relationship, which states that the logarithm of the ratio between the forward and reverse fluxes is directly proportional to the change in Gibbs energy due to a reaction (ΔrG′). Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
388
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 284 publications
(394 citation statements)
references
References 91 publications
(133 reference statements)
5
388
1
Order By: Relevance
“…Indeed, it has been suggested that mdh evolved a high k cat value to compensate for a thermodynamically unfavorable reaction in the direction of the tricarboxylic acid cycle, which causes much backward flux in vivo. This may result in reduction in the k vivo max , which is not accounted for under in vitro conditions (21). Other outliers serve as good candidates for in-depth biochemical analysis.…”
Section: Significancementioning
confidence: 99%
“…Indeed, it has been suggested that mdh evolved a high k cat value to compensate for a thermodynamically unfavorable reaction in the direction of the tricarboxylic acid cycle, which causes much backward flux in vivo. This may result in reduction in the k vivo max , which is not accounted for under in vitro conditions (21). Other outliers serve as good candidates for in-depth biochemical analysis.…”
Section: Significancementioning
confidence: 99%
“…All energy-conserving electron bifurcation reactions were neglected in this analysis. The max-min driving force (MDF) is the lowest value of −Δ r G′ in the pathway [i.e., the reaction(s) with the smallest chemical driving force], after optimizing reactant concentrations within a physiological range (1 μM to 10 mM for noncofactors) as described in the SI Appendix, SI Materials and Methods and Bar-Even et al (37). The cytoplasmic concentration of formate was assumed to be 10 mM.…”
Section: Enzyme Engineeringmentioning
confidence: 99%
“…This can be explained by the fact that during growth of C. autoethanogenum on H 2 /CO 2 or fructose, the function of the enzyme is to catalyze the endergonic reduction of CO 2 to CO (E 0 = ϭ Ϫ520 mV) with reduced ferredoxin (E 0 = ϭ Ϫ400 mV), a step in the total synthesis of acetate from 2 CO 2 , whereas during growth on CO the function of the enzyme is to catalyze the exergonic oxidation of CO to CO 2 with ferredoxin. The Haldane equation predicts that the catalytic efficiency (k cat /K m ) of the enzyme to oxidize CO divided by the catalytic efficiency of the enzyme to reduce CO 2 is equal to the equilibrium constant (57,58).…”
Section: Ferredoxin-dependent Transhydrogenase (Nfnmentioning
confidence: 99%